In situ Be-10, Al-26, and Ne-21 measurements of detrital river sediment in central Cuba - Campbell, Mae Kate; Bierman, Paul R; Schmidt, Amanda H; Sibello Hernández, Rita Yvelice; Garcia-Moya, Alejandro; Corbett, Lee B; Hidy, Alan J; Cartas Aguila, Héctor Alejandro; Guillén Arruebarrena, Aniel; Balco, Greg; Dethier, David; Caffee, Marc W (PANGAEA, 2022)
We measured the concentration of in situ Be-10 and Al-26 in quartz separated from medium (250-850 micron) detrital river sand collected from 22 watersheds in central Cuba. Samples were collected in summer 2018 from watersheds ranging in size from 2 to 730 km². Be and Al extraction was completed at the University of Vermont Community Cosmogenic Facility and accelerator mass spectrometer measurements were made at PRIME Lab. Many of the sampled basins are low slope (average < 1 degree) and underlain by marine rocks. Samples are from the same locations as published chemical weathering rates inferred from dissolved loads in river water (Bierman et al. 2020).
Keywords: Caribbean; Cosmogenic nuclide; cosmogenic radionuclides; erosion; erosion rate; Tropical; tropics